1997
DOI: 10.7164/antibiotics.50.162
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity Relationships of Carbapenem Compounds to Anti-Haemophilus influenzae Activity and Affinity for Penicillin-binding Proteins Effect of 1.BETA.-Methyl Group and C-2 Side Chain.

Abstract: The anti-i/. influenzae activity of meropenem(la) was muchhigher than those of imipenem (4), panipenem (2b) and biapenem (7). To clarify the major structural features responsible for the anti-i/. influenzae activity of carbapenem compounds,the structure-activity relationship to the anti-//. influenzae activity was investigated. The anti-//. influenzae activities of meropenem(la) and l/?-methyl-panipenem (2a) were much higher than those ofdesmethyl-meropenem (lb) and panipenem (2b), respectively. Two carbapenem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Therefore, it is suggested that the antibacterial activity of the other carbapenems against H. influenzae may have further declined due to a recent increase in the number of BLNAR strains. Differences in the binding affinity of carbapenems to H. influenzae PBP3A and PBP3B are considered to play a role in the differences in their antibacterial activity against H. influenzae [14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that the antibacterial activity of the other carbapenems against H. influenzae may have further declined due to a recent increase in the number of BLNAR strains. Differences in the binding affinity of carbapenems to H. influenzae PBP3A and PBP3B are considered to play a role in the differences in their antibacterial activity against H. influenzae [14].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the activity of high‐molecular weight PBPs (transpeptidases) results in abrogation of peptidoglycan crosslinking and is thought to ultimately contribute to the bactericidal activity of β‐lactams through loss of cell wall integrity . Additionally, different β‐lactams have differing affinities for the different types of PBP that a given bacteria may possess . Among the most clinically relevant gram‐negative bacteria, such as Escherichia coli and P. aeruginosa , imipenem generally exhibits the highest affinity for PBP 2, followed by 1a, 1b, and 3 …”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…[33][34][35] Additionally, different β-lactams have differing affinities for the different types of PBP that a given bacteria may possess. [36][37][38][39] Among the most clinically relevant gram-negative bacteria, such as Escherichia coli and P. aeruginosa, imipenem generally exhibits the highest affinity for PBP 2, followed by 1a, 1b, and 3. 31,40 Relebactam β-Lactamases contribute to antimicrobial resistance by directly inactivating β-lactams through the catalyzing of the hydrolysis of the β-lactam ring, thus reducing the amount of active drug available for inhibition of PBP.…”
Section: Imipenemmentioning
confidence: 99%
“…In contrast, MICs above the pneumonia breakpoint [7,8] were observed for the other carbapenems, mainly against the gBLNAR strains. Discrepancies in the susceptibility of H. influenzae to carbapenems are thought to be due to the differences in their binding affinities to H. influenzae PBP3A and PBP3B [18]. H. influenzae is the second most dominant pathogen responsible for CAP in Japan [15].…”
Section: Discussionmentioning
confidence: 99%